Morphometric characteristics of latitude parameters of the middle cranial fossa of mature age human depending on extreme type of skull structure - I. V. Chekanova; O. Yu. Vovk; S. S. Malakhov; S. O. Dubina (Kazimierz Wielki University, 2021)
The study of the structure, shape and size of the skull and its individual structures is in great demand not only from the point of view of expansion of knowledge of craniology, but also modern practical medicine. This is due to the rapid development of new methods for diagnosing pathological processes and the development of less traumatic methods of surgical treatment. The purpose of this study is to establish the size of the transverse parameters of the middle cranial fossa of a mature person depending on the three extreme types of skull. The research was conducted using a study of 50 craniotomograms and 50 bone preparations of the skull of men and women of mature age. The studied material was divided into three groups from the standpoint of studying individual anatomical variability. In order to achieve the goal of the study, the transverse parameters of the middle cranial fossa of mature people at different levels and from both halves were measured. The established indicators of transverse dimensions show that all latitudinal parameters tend to increase from the anterior parts of the middle cranial fossa to the posterior parts. The results of the study also show that the total latitudes and transverse dimensions of the left and right parts of the middle cranial fossa predominate in brachicrans and gradually decrease to dolichocrans with average values in mesocrans. This coincides with the fact that the brachycrane has a short and wide skull shape, the dolichocrane has an elongated and narrow one, and the mesocrane has average skull length and width values. The results of this study significantly supplement the existing information on the individual anatomical variability of the middle cranial fossa of a mature person and also allow more detailed application of these data in practical medicine.